Proximate Composition and Organoleptic Properties of Pumpkin (Cucurbita Moschata)-Based Complementary Foods with Several Types of Nuts - Mardiah; Retno Kartika Rosdiana; Tiana Fitrilia (Indonesian Journal of Applied Research (IJAR), 2022)
Complementary Foods is food given to infants aged 6-24 months. Complementary foods must fulfill the criteria for nutritional needs that have been regulated by the government such as adequacy of macro and micro nutrients. One of the local food ingredients that can be used as complementary foods is pumpkin.Pumpkin is known to contain nutritional components that are quite complete but have a small protein content. Therefore, it is necessary to add nuts as a source of protein. The purpose of this study was to determine the comparison effect of pumpkin puree with various types of nuts on the proximate composition and organoleptic properties of complementary foods. This study used a completely randomized design with one factor, namely the differences in the type of bean puree with five levels of treatments, A1 (35% pumpkin: 35% Bambara bean), A2 (35% pumpkin: 35% kidney bean), A3 (35% pumpkin: 35% mung bean), A4 (35% pumpkin: 35% soybean), and A5 (35% pumpkin: 35% edamame bean). Data analysis using analysis of variance and Kruskall Wallis test. The result showed that the Complementary Foods formulations made with 35% pumpkin puree and 35% soybean puree had the highest nutritional content. The Complementary Foods had 57.25% water content, 2.83% ash content, 20.62% protein content, and 10.49 fat content which had fulfill the Complementary Foods standard except the carbohydrate content. The addition of nuts puree to pumpkin complementary foods had an effect on color and texture sensors and all parameters in the hedonic test.